FIZ AutoDoc – the customer-oriented document delivery service. Issue 3 (17th August 2015) - Hauser, Robert
Abstract : Purpose: – To describe both the service and recent developments of FIZ AutoDoc. Design/methodology/approach: – An in depth description with particular emphasis on copyright issues. Findings: – That FIZ AutoDoc has developed to respond to the information needs of its customers primarily in the commercial sector internationally. Originality/value: – A full description of a valuable service that draws upon the resources of many partners to provide commercial organizations with the information that they need.